2017
DOI: 10.1016/j.cmi.2016.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Methicillin-resistant Staphylococcus aureus among animals: current overview

Abstract: Currently, methicillin-resistant Staphylococcus aureus (MRSA) is a universal threat. After being well established in the healthcare setting, it has emerged in the community among people with no risk factors for MRSA acquisition, therefore imposing a new threat. The subsequent detection of MRSA colonizing or infecting animals as well as in food of animal origin was of major concern, revealing new reservoirs for MRSA. The major MRSA clonal lineages circulating in the different settings, i.e. in hospitals, in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
184
4
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 222 publications
(215 citation statements)
references
References 63 publications
5
184
4
1
Order By: Relevance
“…Furthermore, recent detection of a mecA homologue, designated mecC, was detected among wild animals and water samples with a wide geographical distribution in Europe. 4 The pattern of antimicrobial susceptibility varies according to the degree and duration of livestock exposure to antimicrobials. 5 Since antimicrobials are commonly used in livestock as growth promoters, such exposure is threatening because it facilitates the evolution of antimicrobial resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, recent detection of a mecA homologue, designated mecC, was detected among wild animals and water samples with a wide geographical distribution in Europe. 4 The pattern of antimicrobial susceptibility varies according to the degree and duration of livestock exposure to antimicrobials. 5 Since antimicrobials are commonly used in livestock as growth promoters, such exposure is threatening because it facilitates the evolution of antimicrobial resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Commonly, ST121 isolates are MSSA that are susceptible to methicillin [28, 29]. In contrast to ST121, strains of ST398 could be further grouped into healthcare-associated, community-associated and livestock-associated strains [1, 2, 5, 6]. Among them, the livestock-associated MRSA ST398 was highly concerned for the transmission to humans from animals [5].…”
Section: Discussionmentioning
confidence: 99%
“…In humans, S. aureus is usually associated with skin and soft-tissue infections, endovascular infections, pneumonia, septic arthritis, endocarditis, osteomyelitis and sepsis [1]. The colonisation of S. aureus in animals has been receiving comprehensive attention since animals may potentially act as a reservoir of human infection [5, 6]. …”
Section: Introductionmentioning
confidence: 99%
“…New clones of MRSA will continue to evolve because of selective pressure exerted upon them by the environment and horizontal gene transfer. Methicillin resistant Staphylococcus aureus is constantly evolving and increasingly becoming a global threat, the pathogen is no longer restricted to the hospital setting as previously reported Aires-de-Sousa, (2017). This is because, MRSA has been isolated among individuals without the apparent identifiable risk factors of MRSA acquisition.…”
Section: Acquisition Of Resistances Determinants and The Evolution Ofmentioning
confidence: 98%
“…Molecular typing showed that some animal lineages are host specific while others are able to colonize or infect a wide variety of animals including humans. Studies on the clonal evolution of MRSA has shown that some MRSA lineages are host specific while others are not (Bitrus et al, 2016;Aires-de-Sousa, 2017). The isolation of MRSA from pets in the late 1990s provided sufficient evidences in the clonal dissemination of the pathogen, this is because, prior to this, MRSA is hardly isolated from pets.…”
Section: Acquisition Of Resistances Determinants and The Evolution Ofmentioning
confidence: 99%